2015
DOI: 10.1111/cea.12417
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sublingual immunotherapy with Dermatophagoides farinae vaccine in a murine atopic dermatitis model

Abstract: The mouse model induced by Der f allergen extract reflected the typical hallmarks of human AD. In the Der f allergens-sensitized mice, SLIT treatment with Der f vaccine was shown to significantly inhibit AD symptoms through correction of Th2 and Th1 cytokine predominance. Our study suggested that SLIT could be considered as an attractive treatment for patients with extrinsic AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
4
5
0
Order By: Relevance
“…4,16 According to our previous animal model and other reports, IgE was elevated in mice sera before allergen sensitization and was decreased after treatment. 8,17 Similar findings were observed after LNIT with DNDp. Significantly, decreased Der p-specific IgE may be due to decreased production of IL-4 in Th2 cells.…”
Section: Discussionsupporting
confidence: 72%
“…4,16 According to our previous animal model and other reports, IgE was elevated in mice sera before allergen sensitization and was decreased after treatment. 8,17 Similar findings were observed after LNIT with DNDp. Significantly, decreased Der p-specific IgE may be due to decreased production of IL-4 in Th2 cells.…”
Section: Discussionsupporting
confidence: 72%
“…133 Another group of authors has investigated SLIT in AE patients allergic to HDM in a murine model. 134 The mouse model induced by Der f allergen extract reflected the typical hallmarks of AE in humans. In the Der f allergens-sensitized mice, SLIT treatment with Der f vaccine significantly inhibited AE symptoms through correction of Th2 and Th1 cytokine predominance; therefore according to the authors, SLIT could be considered as an alternative treatment for patients with extrinsic AE.…”
Section: Evidence From Controlled Clinical Trialsmentioning
confidence: 99%
“…Another group of authors has investigated SLIT in AE patients allergic to HDM in a murine model . The mouse model induced by Der f allergen extract reflected the typical hallmarks of AE in humans.…”
Section: Allergen‐specific Immunotherapymentioning
confidence: 99%
“…Liu et al. examined the efficacy of SLIT with Dermatophagoides farinae vaccine in a murine model of atopic dermatitis (AD). The authors showed that SLIT treatment comprising repeated administration of D. farinae extract markedly reduced Th2 cytokine production, eosinophilic inflammation and clinical and histopathologic symptoms of AD.…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%
“…Specific allergen immunotherapy, particularly sublingual immunotherapy (SLIT), has emerged as a treatment of allergic diseases [50], and there is significant clinical evidence that SLIT reduces symptoms in people with AR, allergic conjunctivitis, asthma and insect sting allergy. Liu et al [51] examined the efficacy of SLIT with Dermatophagoides farinae vaccine in a murine model of atopic dermatitis (AD). The authors showed that SLIT treatment comprising repeated administration of D. farinae extract markedly reduced Th2 cytokine production, eosinophilic inflammation and clinical and histopathologic symptoms of AD.…”
Section: Molecular Understanding Of Immunotherapymentioning
confidence: 99%